Impact of Pre-Analytical Conditions on the Antigenicity of Lung Markers: ALK and MET. Issue 5 (May 2020) - Miller, Rachel; Thorne-Nuzzo, Trish; Loftin, Isabell; McElhinny, Abigail; Towne, Penny; Clements, June
Abstract : Diagnostic assays for molecular alterations highly correlated with prognosis, predictive efficacy or safety of therapeutics are valuable clinical tools and in some cases approved as companion diagnostics (CDx) by the Federal Food and Drug Administration. For example, assays that determine echinoderm microtubule-associated protein-like 4 (EML4)-anaplastic lymphoma kinase (ALK) translocation status have been approved as CDx assay for therapies that target this molecular alteration. Characterizing the parameters that may compromise diagnostic accuracy for molecular biomarkers is critical for optimal patient care. To investigate the impact of pre-analytical handling and processing of tumor tissue on commonly used diagnostic immunohistochemistry-based assays for ALK and mesenchymal epithelial transition protein [c-mesenchymal epithelial transition (c-MET)], we investigated the effects of cold ischemia, fixative type, fixation time, and cut-slide age on staining consistency and intensity using human lung xenograft tumor tissue. Cold ischemia times for up to 5 to 6 hours for c-MET or ALK, respectively had minimal impact on staining. The optimal fixation conditions for both assays were found to be at least 6 hours and up to 48 hours for c-MET or 72 hours for ALK, in 10% neutral buffered formalin and Zinc formalin. The ALK antigen demonstrated marked staining intensity differences across non-neutral buffered formalin fixative types and times. Finally, cut-slide age influenced assay performance for both ALK and c-MET, with maximum stability observed when cut slides were stored at ambient temperatures (30°C) for no longer than 3, and 5 months, respectively. This study highlights the potential for pre-analytical factors to confound diagnostic test result interpretation. Abstract : Supplemental Digital Content is available in the text.